Perancangan sistem kendali motor DC dengan Fuzzy menggunakan Simulink Matlab : Design of DC motor control system with Fuzzy using Simulink Matlab - Hadi, Bagus Dharmawan; Kurnianingtyas, Rahajeng (Elektriese: Jurnal Sains dan Teknologi Elektro, 2025)
This study examines the application of Fuzzy Logic Controller (FLC) to optimize the performance of Direct Current (DC) motors. DC motors offer advantages such as high starting torque and ease of maintenance, making them suitable to replace oil-fueled engines that contribute to pollution and global warming. The transition to electric vehicles is supported by advances in battery technology, which provides reliable DC electricity. An important aspect of using DC motors in vehicles is speed control, which is essential for optimizing performance. FLC provides an alternative by using fuzzy rules for decision making, improving stability, accuracy, and dynamic response under various conditions. This study aims to determine the optimal control parameters for DC motors using FLC. The results showed that the rise time was around 1.05 seconds and the settling time was around 1.1 seconds. Simulations performed in Simulink Matlab showed that FLC allows the system to reach the desired point with minimal overshoot.